Negotiating Academic Legitimacy through Politeness and Authorship Ethics: A Micro-Analytic Study of Digital Academic Communication: Arie Yuandani, I Made Juliarta (Universitas Bali Dwipa, 2026)
This article examines a short digital interaction between an early-career researcher and a senior linguistics lecturer in order to explore how academic legitimacy, politeness, and authorship ethics are negotiated in everyday scholarly communication. Although the interaction takes place in an informal WhatsApp exchange, it reveals that linguistic choices are not merely interpersonal ornaments but also ethical and epistemic strategies within hierarchical academic relations. Using Brown and Levinson’s Politeness Theory together with COPE and ICMJE authorship principles, this study adopts a micro-analytic autoethnographic approach to examine how lexical mitigation, syntactic softening, and implied meanings work to manage face threats, defer premature authorship claims, and protect intellectual autonomy. The analysis suggests that politeness in this context functions as a practical ethical resource that helps regulate the pace of scholarly claims and maintain integrity in asymmetrical academic relationships.